Use of Health Care Services and Associated Factors among Women. - Nader Esmailnasab; Jafar Hassanzadeh; Shahab Rezaeian; Mehrdad Barkhordari (Tehran University of Medical Sciences, 2014)
To estimate the prevalence and analyze factors associated with both public and private health services utilization in women population in a western district of Iran.A cross-sectional study with 1200 individuals aged 18-49 years carried out in different districts of Sanandaj City, western Iran, in 2012. The main outcome variable was use of health service in the previous 12 months. The in-dependent variables were age, education level, place of residence, marital and pregnancy status, household wealth, oc-cupation and duration time of employment, and rating of quality of health services.The prevalence of public and private health services utilization were 60.8% [95%CI: 57.8, 63.8] and 53.8% [95%CI: 50.8%, 56.8%], respectively (P=0.001). After controlling other investigated factors using logistic regression; the academic educational level (OR=1.36, 95%CI: 1.03, 1.80; OR=1.76, 95%CI: 1.33, 2.33), residents of urban (OR=1.65, 95%CI: 1.10, 2.47; OR=1.60, 95%CI: 1.10, 2.42), pregnancy status (OR=2.38, 95%CI: 1.60, 3.55; OR=2.36, 95%CI: 1.61, 3.47), and high level of quality of health services (OR=1.61, 95%CI: 1.15, 2.27; OR=1.70, 95%CI: 1.20, 2.40) were found to be predictors of utilization of both public and private health care respectively. There was also statistically relation between high level of household wealth (OR=3.01, 95% CI: 2.00, 4.57) and private health services utilization.Prevalence of health services utilization varied according to the individual and social factors of popula-tion studied. Present study emphasizes the need to develop care models that focus on the characteristics and demands of the subjects.